2010
DOI: 10.1200/jco.2010.28.1444
|View full text |Cite
|
Sign up to set email alerts
|

Phase III, Randomized, Double-Blind, Placebo-Controlled Study of Long-Acting Methylphenidate for Cancer-Related Fatigue: North Central Cancer Treatment Group NCCTG-N05C7 Trial

Abstract: Purpose Fatigue is one of the most common symptoms experienced by patients with cancer. This trial was developed to evaluate the efficacy of long-acting methylphenidate for improving cancer-related fatigue and to assess its toxicities. Patients and Methods Adults with cancer were randomly assigned in a double-blinded manner to receive methylphenidate (target dose, 54 mg/d) or placebo for 4 weeks. The Brief Fatigue Inventory was the primary outcome measure, while secondary outcome measures included a Symptom Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
0
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(115 citation statements)
references
References 49 publications
4
102
0
9
Order By: Relevance
“…23 Psychostimulants have demonstrated mixed efficacy for improving fatigue, [24][25][26] and can cause additional problems such as agitation or low appetite. 27 The results of the current study support the importance of advancing the science of fatigue and other complex symptoms that occur within the context of cancer treatments.…”
Section: Discussionsupporting
confidence: 63%
“…23 Psychostimulants have demonstrated mixed efficacy for improving fatigue, [24][25][26] and can cause additional problems such as agitation or low appetite. 27 The results of the current study support the importance of advancing the science of fatigue and other complex symptoms that occur within the context of cancer treatments.…”
Section: Discussionsupporting
confidence: 63%
“…A more recent meta-analysis of methylphenidate treatment for cancerrelated fatigue included five studies (n=426) and demonstrated benefit of methylphenidate over placebo, though with a small effect size [63]. Subsequently, two larger studies of methylphenidate have failed to demonstrate benefit over placebo for cancer-related fatigue [64,65]; but like the aforementioned modafanil study, a subset analysis demonstrated benefit for those patients with severe fatigue and/or advanced disease [65]. Thus, the data is limited regarding the efficacy of pharmacologic treatments for fatigue in cancer.…”
Section: Pharmacologic Treatment Of Cancer-related Fatiguementioning
confidence: 99%
“…Hardy revisa los efectos secundarios de estudios que versan sobre metilfenidato entre 1956 y 2009. Los más frecuentemente descritos son el nerviosismo/insomnio y anorexia 8,16,19 , taquicardia-palpitaciones, mareo-confusión 8,19 . Otros como cefalea o diarrea/dolor abdominal 15 pueden llegar a presentarse hasta en un 63% de los casos (siendo el estudio de Roth 9 , el más reciente EC con mayor incidencia de efectos secundarios).…”
Section: Estudios Clínicos Sobre Efectos Secundarios Y Tolerabilidadunclassified